The influence of NK cell-mediated ADCC: Structure and expression of the CD16 molecule differ among FcγRIIIa-V158F genotypes in healthy Japanese subjects - Oboshi, Wataru; Watanabe, Toru; Matsuyama, Yuumi; Kobara, Ayana; Yukimasa, Nobuyasu; Ueno, Ichiro; Aki, Kensaku; Tada, Tomoki; Hosoi, Eiji (Human immunology, 2016)
NK cells express the CD16 (FcγRIIIa) receptor, which mediates antibody-dependent cellular cytotoxicity (ADCC), on their cell surface. Therefore, ADCC activity may be influenced by qualitative or quantitative changes in the CD16 molecule on NK cells. Responses to NK cell-mediated ADCC have been shown to depend on single nucleotide polymorphisms (SNPs) at FcγRIIIa amino acid position 158. However, a consensus has not yet been reached regarding differences in the structure and expression levels of the CD16 molecule among FcγRIIIa-V158F genotypes, which have not yet been adequately investigated in healthy Japanese individuals. We herein examined the influence of the FcγRIIIa polymorphism on ADCC, binding affinity of CD16 to the Fc region, FCGR3A gene expression, and cell-surface CD16 expression in healthy Japanese subjects. FcγRIIIa-V158F genotyping was performed for 101 subjects. The results obtained showed that all parameters analyzed increased in the order of V/V>V/F>F/F and were significantly higher in V/V subjects than in F/F subjects. Moreover, a positive correlation was observed between ADCC activity and binding affinity, FCGR3A transcript levels, and surface CD16 expression levels. These results suggest that the structure and expression of the CD16 molecule differs among FcγRIIIa-V158F genotypes, and the FcγRIIIa-V158F polymorphism may be represent a haplotype with other SNPs in regulatory regions in Japanese subjects.